Ureteral Papilla Implantation as a Technique for Neoureterocystostomy in Cats Undergoing Renal Transplantation: 30 Cases. Issue 4 (May 2016) - Sutherland, Brian J.; McAnulty, Jonathan F.; Hardie, Robert J.
Abstract : Objective: To describe the clinical outcome of donor and recipient cats undergoing ureteral papilla harvest and implantation as a technique for neoureterocystostomy in clinical kidney transplant. Study Design: Retrospective case series. Animals: Donor (n=31) and recipient (n=30) cats that underwent kidney harvest and transplantation using ureteral papilla implantation technique for neoureterocystostomy. Methods: Medical records for donor and recipient cats presented to the University of Wisconsin Veterinary Teaching Hospital from January 2003 to December 2014 were reviewed. Data recorded included complete blood count, serum chemistry panel, surgical technique, diagnostic imaging results, short‐ and long‐term complications, and anesthetic survival. Results: All 30 recipients recovered from anesthesia. Four died within 24 hours and 26 survived to hospital discharge. Serum creatinine was within the reference interval by 72 hours in 22/26 cats (85%). Complications related to the ureteral papilla implantation technique were seen in only 1 cat (3%). Uroabdomen diagnosed on day 3 ultimately resolved over the following 24 hours without surgical intervention. All 31 donor cats survived to discharge. Four donors (13%) experienced mild, transiently increased serum creatinine. Conclusion: Ureteral papilla implantation is a viable technique for neoureterocystostomy in cats undergoing kidney transplantation. Proposed benefits for the recipient include a less technically challenging anastomosis, decreased risk of ureteral obstruction at the anastomosis site, and reduced risk of leakage compared to previous reports. Benefits for recipients should be weighed against risks to donors, including a more complex ureteral harvest, increased surgical time, and potential injury or obstruction of the contralateral ureteral papilla.